The Other in the Axiological Educational Space - Agata Cudowska (Lubelski Rocznik Pedagogiczny, 2018)
The article presents a personalistic approach to education as a meeting and subjective relationship. The understanding of another in the space of dialogue is characterized. The axiological sense of the meeting and the educational relation as the experience of the other person and experiencing the values that accompany it are described. The author focuses on the phenomenological approach to education, which is based on responsibility as a fundamental bond with others. The need to build a space for dialogue in upbringing on the virtue of responsibility, freedom and justice is emphasized. Attention is paid to the need for creative understanding in a dialogic educational relationship, it is emphasized that experiencing another is inscribed in educational processes and creates an axiological educational space.